Complex Anorectal Disorders Investigation and Management - Wexner, Steven D.; Zbar, Andrew P.; Pescatori, Mario; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2005)
A large cross-section of the world’s great and good in colorectal surgery have been enticed, inveigled, I suspect at times brow-beaten, to produce this tour de force. The editors, themselves famous for their own extensive contributions in this area, must be congratulated for their ?ne achievements. Every card-carrying specialist needs a reference book of this sort. My own are well worn by many years’ reference, for when confronted by big problems, big issues, senior clinicians must be able to lay their hands on a well-thumbed old favourite: not a small,“where are we now” sort of book, or an exam crammer, but on one that is large, sedate and of “traditional build. ” Rather than being a supergiant covering all of colorectal surgery, this book has focused on the broad structural investigation of the anorectum and on the focused management of largely “functional” problems. And it has done so in style. For this is a core area of specialist practice;your more general colleagues may think twice before referring you new cases of cancer and in?ammatory bowel disease (both also central areas in colorectal surgery), but they will not hesitate in referring the patients whose inves- gation and management are described here. And they will expect you to know how to deal with them. These are some of the most challenging patients to manage. Rightly have the editors covered the physiological areas,rightly the psychological issues, rightly the medicolegal aspects: here is the making of a specialist—the sword and the shield.
Anorectal Testing -- Anorectal Anatomy: The Contribution of New Technology -- History, Clinical Examination, and Basic Physiology -- Rectoanal Inhibition -- Vectorvolume Manometry -- Clinical Rectal Compliance Measurement -- Impedance Planimetry: Application for Studies of Rectal Function -- Impedance Planimetry: Clinical Impedance Planimetry -- Ambulatory Manometry -- The Use of Colonic Motility and Transit Studies -- Anorectal Sensitivity -- Neurophysiology in Pelvic Floor Disorders -- Evacuation Proctography -- Defecography: A Swedish Perspective -- Ultrasound in Coloproctologic Practice: Endorectal/Endoanal Ultrasound -- Ultasound in Coloproctologic Practice: Dynamic Transperineal Ultrasound and Transvaginal Sonography -- Three-Dimensional Endoanal Ultrasound in Proctological Practice -- MRI in Colorectal Surgery: Surface Magnetic Resonance Imaging in Anorectal Practice -- MRI in Colorectal Surgery: Endoluminal MR Imaging of Anorectal Diseases -- MRI in Colorectal Surgery: Dynamic Magnetic Resonance Imaging -- Sphincter Pharmacology and Pharmacotherapy -- Anal Histopathology -- Anal Intraepithelial Neoplasia (AIN) -- Clinical Anorectal Assessment -- An Overview -- Managing Slow-Transit Constipation -- Rectocele -- Anismus -- Biofeedback for Constipation and Fecal Incontinence -- Evacuatory Dysfunction Following Gynecologic Surgery -- An Overview -- Quality of Life Issues -- Fecal and Urinary Incontinence: Epidemiology and Etiology -- Sacral Neuromodulation -- Urogynecological Assessment and Perspective in Patients Presenting with Evacuatory Dysfunction -- Assessing the Postoperative Patient with Evacuatory Dysfunction: Disordered Defecation of the Neorectum and Neorectal Reservoir -- Evaluation and Management of Postoperative Fecal Incontinence -- An Overview -- Managing Functional Problems Following Dynamic Graciloplasty -- Assessing the Functional Results of the Artificial Bowel Sphincter -- Functional Problems in the Patient with a Neurological Disorder -- Psychological Assessment of Patients with Proctological Disorders -- A Practical Guide to Running an Anorectal Laboratory -- Medicolegal Aspects of Coloproctologic Practice.
Keywords: Rectum—Surgery .; Gastroenterology .; Proctology; Urology; Gynecology .; Colorectal Surgery; Gastroenterology; Proctology; Urology; Gynecology